Measurements of plasma spectra from hot dense elements and mixtures at conditions relevant to the solar radiative zone - Hoarty, D; Hill, E; Beiersdorfer, P; Allan, P; Brown, C; Hill, M; Hobbs, L; James, S; Morton, J; Sircombe, N; Upcraft, L; Harris, J; et al. (AIP Publishing, 2017)
X-ray emission spectroscopy has been used to study hot dense plasmas produced using high power laser irradiation of dot samples buried in low Z foils of plastic or diamond. By combining a high contrast short pulse (picosecond timescale) laser beam operating in second harmonic with long pulse (nanosecond timescale) laser beams in third harmonic, and with pulse shaping of the long pulse beams, a range of plasma temperatures from 400eV up to 2.5keV and electron densities from 5e22 up to 1e24/cc have been accessed. Examples are given of measurements of dense plasma effects such as ionization potential depression and line-broadening from the K-shell emission spectra of a range of low Z elements and mixtures and compared to model prediction. Detailed spectra from measurements of the L-shell emission from mid-Z elements are also presented for an example spectrum of germanium. These data are at conditions found in stellar interiors and in particular in the radiative zone of the sun. The plasma conditions are inferred from comparison of the measured spectra to detailed modeling using atomic kinetics and spectral synthesis codes.